2022
DOI: 10.1007/s11686-022-00524-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Scabies in the Covid-19 Pandemic Period and Determination of Risk Factors for Scabies: a Hospital-Based Cross-Sectional Study in Northeast Turkey

Abstract: Background There is an increase in the incidence of scabies in Turkey, which started before the Covid-19 pandemic, and this situation is considered as an epidemic. With this study, we aimed to reveal the prevalence of scabies during the pandemic period and the risk factors that are effective in the transmission of scabies. Methods Our study was performed as a cross-sectional study in 376 patients who applied to our dermatology outpatient clinic between 1st and 30th Apri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
(31 reference statements)
0
7
1
Order By: Relevance
“…Other studies showed some increases during the first months of the COVID-19 pandemic but not to our extent [2-6]. In addition, although in a Spanish hospital the number of patients with scabies increased during the lockdown (March-June 2020) [3,6], we observed an expected number of diagnoses during those months that could be related to less primary care consultations as occurred with other relevant clinical conditions [8].…”
Section: Main Textcontrasting
confidence: 63%
See 3 more Smart Citations
“…Other studies showed some increases during the first months of the COVID-19 pandemic but not to our extent [2-6]. In addition, although in a Spanish hospital the number of patients with scabies increased during the lockdown (March-June 2020) [3,6], we observed an expected number of diagnoses during those months that could be related to less primary care consultations as occurred with other relevant clinical conditions [8].…”
Section: Main Textcontrasting
confidence: 63%
“…First, stay-at-home orders and quarantines probably contributed to more close contacts in households, increasing the risk of transmission [2,3,6,9]. Second, it has been suggested that daily habits including personal hygiene could have changed during the COVID-19 pandemic due to changes in social interactions, the increase of in-home working and the temporary closure of workplaces [2-9]. Not showering regularly and being unemployed were previously identified as risk factors for scabies infestations [2].…”
Section: Main Textmentioning
confidence: 99%
See 2 more Smart Citations
“…This study shows that a rise in the unemployment rate was associated with a higher incidence rate of scabies. Similarly, in study conducted in Poland (2019), the authors emphasized that unemployment is effective on scabies, in a study conducted in Turkey, Ural et al (2022) demonstrated also that scabies was more common in non-working than in working [53,54]. Unemployment is a situation that is expected to affect the socioeconomic status of the family, and therefore, the health, nutrition, housing, etc.…”
Section: Discussionmentioning
confidence: 99%